Infectious Salmon Anemia and Farm-Level Culling Strategies - Qviller, Lars; Kristoffersen, Anja B.; Lyngstad, Trude M.; Lillehaug, Atle (Frontiers in Veterinary Science, 2020)
3 Infectious salmon anemia (ISA) is an infectious disease, and outbreaks must be handled to avoid 4 spread between farms. Intensive culling of infected farms is an important biosecurity measure to 5 avoid further spread, but also a costly intervention that farmers try to avoid. The lack of action 6 however, may lead to new outbreaks in proximate farms, with severe impact on both economy 7 and animal welfare. Here we aim to explore how a time delay between detected outbreaks and 8 culling of both infected cages and entire farms affect the further spread of the disease. We use 9 a previously published model to calculate how many farms that has been directly infected from 10 each outbreak. To investigate the effect of culling on further spread of the disease, we use the 11 number of months spent from the detected outbreak to a) the first cage was depopulated, and 12 b) to the entire farm was depopulated, as predictors of how many new farms the virus transmit 13 to, after controlling for contact between farms. We show that time spent before the first cage 14 was depopulated correlates positively with how many new farms that gets infected, indicating 15 that infected cages should be culled with as little time delay as possible. The model does not 16 yield enough power to separate between culling of only cages assumed to be infected and the 17 entire farm, and consequently no direct empirical evidence for the latter. Lack of evidence is not 18 evidence however, and we argue that a high probability of spread between cages in infected 19 farms still promote depopulation of entire farms as the safest option.